TEM Studies of SPUTTER-DEPOSITED Ni4Al Alloy Thin Films - T. Joseph, Sahaya Anand (2011)
The nanostructural characteristics of direct-current magnetron sputter-deposited Ni4Al alloy films were studied during in situ isothermal annealing in a transmission electron microscope. An expansion of the lattice by nearly 5% was observed for the Ni0.8Al0.2 films in their low-thickness and as-deposited state. The lattice size approaches the bulk value when the film thickness increases or after vacuum annealing heat-treatment. The Ni0.8Al0.2 films have a nanocrystalline structure in which the ordered L12 phase appears upon annealing at above 500°C. The ordered B2 phase Ni4Al phase with orthorhombic structure were found.